In silico SYBR® green-based qPCR primer design for virulent protein C gene of Edwardsiella tarda - Rian Ka Praja; Reny Rosalina (Syiah Kuala University, 2021)
Edwardsiella tarda infection in fish results in economic losses in aquaculture industries worldwide. Besides, this pathogen is also a zoonotic agent causing gastrointestinal disease in humans. Detection of virulence factors expressed by E. tarda is a key for molecular diagnosis. This study aimed to design SYBR®Green-based quantitative PCR (qPCR) primer for E. tarda virulent protein C (EvpC) gene. A sequence of EvpC with accession number AY424360.4:6500-6991 obtained from GenBank NCBI was selected as the basis for qPCR primer design. qPCR primers were designed using Primer3 online software. Further analysis related to the secondary structure of each primer was carried out using Beacon Designer Free Edition. Five pairs of qPCR primers were successfully designed with Primer3. Based on the results of Primer3 and Beacon Designer analysis, F primer pair 1 (5'-GAATCCACCGACGATAAGCACAAA-3') and R primer pair 1 (5'-GACACGCAGCACCGACATCA-3') were the most favorable primer set since this primer met the criteria in terms of length, melting temperature, GC content, and self complementarity. In addition, this primer set had the highest (closest to zero) -ΔG value of cross dimer, self dimer, and hairpin. It can be concluded that SYBR® Green-based qPCR primer set for EvpC has been successfully designed. However, laboratory optimization experiments are essential for this designed primer set.